ANALYSIS OF ERGONOMIC FACTORS WITH NURSES PERFORMANCE AT SEMBIRING DELI TUA HOSPITAL - sembiring, bungamari; Lubis, Fithri Handayani (Jurnal Penelitian Kesmasy, 2024)
Among the many aspects of quality that health care providers around the world are presently concentrating on is patient safety. Nursing care cannot be separated from the pursuit of patient safety. There has been a rise in the importance of nurses playing an active part in improving the standard of nursing care, which has prompted calls for more robust competency standards to back up the safety movement. Reduced occurrences of harm to patients are a direct result of nurses implementing work ergonomics practices. There are many members of the medical community who work to improve people's health, and nurses are no exception. However, while doing their jobs, nurses frequently overlook crucial details that could put them at risk for occupational diseases. Quantitative research with a cross-sectional technique is what's being utilized. All of the nurses working at RSU Sembiring Deli Tua made up the population of this study. There were 156 participants in this study. The findings revealed that most nurses were female, had been in the field for at least four years, and had a reasonable level of job security. They were also mostly in their 30s. It is well-known that the performance of nurses at RSU Sembiring Deli Tua is influenced by factors such as gender, age, length of service, and job position.